Optimization by RSM of reinforced concrete domes with meridian ribs, under static loading. - Logzit N.; Raouache E.; Bentoumi M.; Bentoumi A.; Khababa I. (Selected Scientific Papers: Journal of Civil Engineering)
Reinforced concrete domes with meridian ribs present a suitable solution for covering large spaces, but their optimization in terms of strength and stability remains a challenge not yet mastered. This work presents a new global mathematical approach to optimizing these structures, starting with a primary configuration braced at the top and bottom with ring beams. This configuration will undergo optimization via numerical simulation to ensure its mechanical performance. The main variables studied include dome diameter, rib spacing, thickness and supported load. A Response Surface Methodology (RSM) is then used to correlate these parameters. Ultimately, a cost-oriented objective function is derived, incorporating a load-bearing capacity coefficient. This approach proves effective and can serve as a valuable tool for designers seeking to optimize their projects.